Analisis Makna Tempat Kedudukan Virtual Office dalam Undang-Undang Perseroan Terbatas - Makmun, Tasya Melia Valetiningtyas; Santoso, Budi; Kurniaty, Rika (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2023)
this study aimed at analyze the meaning of the location of a virtual office based on the Limited Liability Company Law. The research method used in this research is a normative juridical method with statutory approach and comparative approach. The domicile is a city or district within the territory of the Republic of Indonesia as determined in the Company’s articles of association. Includes a conventional office address owned by a Limited Liability Company which functions as a condition for establishing a Limited Liability Company as well as a correspondence address. Virtual offices are one of the impacts of the development of e-commerce. Virtual office is a solution for companies as a work space to carry out company activities online. The legal relationship related to virtual offices is civil with the service provider. The domicile in limited liability company law does not include virtual offices because there are very basic differences such as ownership of a virtual office which can be owned by more than one party.